SIZE, SEX AND LENGTH AT MATURITY OF FOUR COMMON SHARKS CAUGHT FROM WESTERN INDONESIA - Fahmi, -; Sumadhiharga, Kurnaen (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
A study on four common shark species in Indonesia, the spinner shark Carcharhinus brevipinna (Muller and Henle, 1839), silky shark Carcharhinus falciformis (Bibron, 1839), spot-tail shark Carcharhinus sorrah (Valenciennes, 1839) and scalloped hammerhead Sphyrna lewini (Griffith and Smith, 1834) was conducted at several shark landing sites in western Indonesia from March 2002 to December 2004. Data were collected from the surveyed areas including the length of frequency, sex composition and length at maturity. In general, they were caught at size smaller than their maturity size. The proportion of immature C. brevipinna, C. falciformis, C. sorrah and S. lewini to their total number recorded at the surveyed area during the study were about 87%, 50%, 80% and 65%, respectively. According to the length at maturity, females generally attained their maturity in larger size than males. Some factors contributing the catches in immature size and conservation status of those four species were also discussed.